State-building and internal colonialism: A case study of the separatism in Aceh and West Papua, Indonesia - Li, Yuhong; Zheng, Anguang (Masyarakat, Kebudayaan dan Politik, 2023)
Adaptation to the norms of nation-states has always been one of the most important issues for Southeast Asian countries. This paper takes Aceh and Western Papua as examples to explore their interaction with the central government of Indonesia and try to answer why local authorities have different responses after implementing the indirect rule. This study mainly uses process tracking methods to test the interaction between the central and local governments in Indonesia. This study believes that trust is the fundamental factor that determines whether the local authorities and the central government can have a positive interaction. This reason will change the central government in the process of State-building. The study found that Aceh and Western Papua had different feedback to the central government. The key lies in whether they form a "trust” interaction, rather than whether they adopt an inclusive system (democratic system). This study concluded the feedback difference between Aceh and Western Papua as a classic case shows that, as a country, it is not only represented by the central government but also needs the "trust” of the central government and local authorities to form good governance, as well as national development effective.